2014
DOI: 10.3389/fphys.2014.00248
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D: a critical and essential micronutrient for human health

Abstract: Vitamin D is a micronutrient that is needed for optimal health throughout the whole life. Vitamin D3 (cholecalciferol) can be either synthesized in the human skin upon exposure to the UV light of the sun, or it is obtained from the diet. If the photoconversion in the skin due to reduced sun exposure (e.g., in wintertime) is insufficient, intake of adequate vitamin D from the diet is essential to health. Severe vitamin D deficiency can lead to a multitude of avoidable illnesses; among them are well-known bone d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
144
0
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(162 citation statements)
references
References 160 publications
(209 reference statements)
4
144
0
14
Order By: Relevance
“…27,28 En general, habrá que considerar que la insuficiencia de vitamina D corresponde a valores séricos inferiores a 30 ng/ml y que la deficiencia a valores inferiores a 20 ng/ml son los criterios más aceptados a nivel mundial, 13 aunque no necesariamente son considerados los mejores, ya que algunos autores asocian niveles séricos más altos de esta vitamina con efectos protectores contra enfermedades como el cáncer. 2,13 Realizar estudios como el aquí presentado sobre los niveles de vitamina D de la población saludable en un determinado entorno resulta de gran importancia como referencia para futuros estudios de grupos poblacionales comparables pero en otras condiciones de salud.…”
Section: Cuadro Iunclassified
“…27,28 En general, habrá que considerar que la insuficiencia de vitamina D corresponde a valores séricos inferiores a 30 ng/ml y que la deficiencia a valores inferiores a 20 ng/ml son los criterios más aceptados a nivel mundial, 13 aunque no necesariamente son considerados los mejores, ya que algunos autores asocian niveles séricos más altos de esta vitamina con efectos protectores contra enfermedades como el cáncer. 2,13 Realizar estudios como el aquí presentado sobre los niveles de vitamina D de la población saludable en un determinado entorno resulta de gran importancia como referencia para futuros estudios de grupos poblacionales comparables pero en otras condiciones de salud.…”
Section: Cuadro Iunclassified
“…Therefore, patients with low 25(OH)D levels are theoretically considered to have vitamin D deficient rickets or osteomalacia. However, vitamin D deficiency or insufficiency is quite common even in the general population [19], and it is possible that low 25(OH)D levels can be observed in patients with rickets or osteomalacia from other causes. Investigation of 25(OH)D levels in patients with vitamin D deficient rickets and XLH indicated that there was overlap of serum 25(OH)D levels in these patients.…”
Section: Differential Diagnosis Of Causes Of Rickets and Osteomalaciamentioning
confidence: 99%
“…Further studies are needed to investigate these hypotheses and any potential consequences for clinical practice. Most importantly, we are all awaiting the randomized intervention of vitamin D supplementation to be published in the near future ( 8,18 These randomized trials will provide us with definitive answers as to whether vitamin D supplementation will reduce cardiovascular disease or not and whether vitamin D is causally related to cardiovascular disease.…”
Section: See Accompanying Article On Page 2204mentioning
confidence: 99%